Desain Didaktis Luas Daerah Segi Empat Sembarang Berbasis Model Pembelajaran SPADE - Dwi Utami; Epon Nur’aeni; Akhmad Nugraha (Universitas Pendidikan Indonesia Kampus Serang, 2020)
This research was motivated preliminary studies results on non optimal the students’ ability of scalene rectangular area and the obstacle leraning experienced by students. The effort made by the teacher to overcome the learning obstacle is to design learning based on students’ needs and characteristics. In the implementation the teacher should adjust the design in accordance with the classroom situations and conditions. The purpose of this study were to describe the didactic design of scalene rectangular area based on the SPADE learning model for fourth grade students of elementary schools and to describe the implementation and responses of teachers and students toward the didactic design of scalene recrangular area based on the SPADE learning models in elementary schools. The research method used was a qualitative by DDR (Design Didactial Research) model consisting of three stages: prospective analysis, metapedadidactic analysis, and restropective analysis. This research was conducted in the fourth grade. The instrument of data collection used essay question on scalene rectangular area. The results of the study is a teaching materials in form of student activity sheets and lesson plans that were developed as alternatives in primary schools learning to minimize learning obstacles in mathematics learning in forth grade of elementary schools.